Comprehensive Analysis of Prognostic Value and Immune Infiltration of Ficolin Family Members in Hepatocellular Carcinoma - Sun, Liang; Yu, Shian; Dong, Cairong; Wu, Zhengyi; Huang, He; Chen, Zhendong; Wu, Zhipeng; Yin, Xiangbao (Frontiers in Genetics, 2022)
Objective: Ficolin(FCN) family proteins are part of the innate immune system and play a role in the recognition of molecules in the complement system, and are involved in the development of tumors. The mechanism of immunotherapy in liver hepatocellular carcinoma is still unclear. Methods: In this study, we used TCGA database, HPA database, GEPIA, Kaplan-Meier plotter, TCGAportal, cBioPortal, GeneMANIA, TIMER and TISIDB, The Ficolin family proteins (FCN1, FCN2 and FCN3, FCNs) were analyzed in terms of expression differences, prognostic value, gene changes, functional enrichment and correlation analysis of immune factors in patients with liver hepatocellular carcinoma. Results: In patients with hepatocellular carcinoma, the expression level of FCN1/2/3 was significantly reduced. Among them, FCN3 was significantly correlated with overall survival (OS), progression-free survival (PFS) and relapse-free survival (RFS) in HCC patients. FCN1 showed significant correlation with PFS and RFS. FCN1 and FCN3 may be potential prognostic markers of survival in patients with liver hepatocellular carcinoma. In addition, the function of differentially expressed FCNs is mainly related to complement activation, immune response, apoptotic cell clearance and phagocytosis. FCNs was found to be correlated with a variety of immune cell infiltrates, and there was a correlation between FCNs and related immune factors. The expression of FCN1 and FCN3 was significantly different in immune cell and stromal cell component scores in liver hepatocellular carcinoma. Analysis of the correlation between FCNs and tumor mutation burden (TMB) and microsatellite instability (MSI) of Pan cancer suggested that FCN3 was significantly correlated with both in LIHC. Conclusions: Our study provides new insights into the association between the FCN family and immunotherapy for hepatocellular carcinoma, FCN3 may be a prognostic biomarker and immunotherapy target for liver hepatocellular carcinoma.